Assessing Perception And Attitude Of Supporting Of Enterprises Regarding The Continued Application Of E-Tax In Vietnam - OANH, THAI THI KIM; THUY, NGUYEN THI LE; SONG, NGUYEN VAN; YEN, MAC THI HAI; HANG, NGUYEN THANH; HUONG, NGUYEN THI THU (The journal of contemporary issues in business and government, 2021)
The study is based on a combination of the Theory of Reasoned Action (TRA) and Diffusion of innovation theory (DOI) to assess the perception and attitude of supporting of enterprises regarding the continued application of e-tax in Vietnam. Based on the reliability analysis of Cronbach's Alpha, EFA analysis, correlation analysis, and linear regression analysis, the research will provide experimental evidence to determine the level of perception and attitude of supporting of the enterprises, and factors affecting the perception and attitude of continued applying e-tax. The results show that the perception and attitude of continued applying e-tax of enterprises are on average level; attitude towards the continued application of e-tax by enterprises is positively influenced by perceptions of the benefits of e-tax, the compliance of e-tax, the ease of use of e-tax and negatively affected by the perceived risk of e-tax; the intention to continue applying e-tax is strongly influenced by (1) the attitude of continued use, (2) behavioral attitudes and (3) voluntary attitude of continued application of e-tax. Based on the results of analysis and verification of survey data, the study proposes appropriate recommendations to maintain and develop the application of e-tax in Vietnam; contribute to tax administrative reform; facilitate enterprises in tax-paying; and improve the national competitiveness index in the tax field.